PEMANFAATAN BUBUR BUAH NANAS DALAM PEMBUATAN ES KRIM - Lesmana, Resti; Pato, Usman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Ice cream is frozen food made from milk fat, sweeteners, flavorings, and other additives such as nuts, fruits, or candies. The objective of this research was to find the optimal pineapple pulp addition on the physicochemical and sensory properties of ice cream. This study used completely randomized design (CRD) experiment with four treatments and four replications. The treatments used for making ice cream were E0 (without the addition of pineapple slurry), E1 (addition of 3% pineapple), E2 (addition of 6% pineapple), and E3 (addition of 9% pineapple). The data obtained were analyzed statistically using ANOVA and DNMRT at 5% level. The results showed that the addition of pineapple slurry significantly affectedoverrun, melting time of ice cream,fiber and fat contents, and the descriptive sensory assessmentincluding color, flavor, aroma, texture, and hedonic assessment of overall acceptance of ice cream. The selected pineapple fruit ice cream of treatment E1 (3% pineapple fruit addition) has 34.46% overrun, 16.38 minute melting time, 0.48% fiber content, and 4.00% fat content, and overall sensory assessment liked by panelists. Keywords:Pulp pineapple, ice cream.